(Re-)shaping learning experiences in supply chain management and logistics education under disruptive uncertain situations - Salinas-Navarro, David Ernesto; Pacheco-Velazquez, Ernesto; da Silva-Ovando, Agatha Clarice (Frontiers in Education, 2024)
Frequently, disruptive uncertain events have compelled universities to unexpectedly transition from face-to-face to remote online learning experiences to sustain their academic activities. However, this shift creates instructional and learning challenges and limitations. Remote online instruction typically becomes monotonous and challenging for students due to their limited social interaction, insufficient access to educational resources, and reduced practical activities, thereby jeopardizing the achievement of intended learning outcomes. To address this issue, this work presents an experiential learning framework aimed at creating active learning experiences that enhance student motivation and engagement by incorporating disruptive uncertain events as study situations for relevant learning. To illustrate their implementation, a methodology is proposed, including a framework for designing learning experiences. Accordingly, the case of a learning experience is presented concerning supply chain disruptions during the COVID-19 pandemic for supply chain management and logistics education at a private university in Bolivia. Results suggest that the novel learning experience positively impacted student motivation and engagement while achieving their intended learning outcomes. However, further instances of learning experiences are required to identify similarities or invariances that recognize the applicability of the proposed method and conceptualizations in other contexts and situations.